New Insights on Biofilm Antimicrobial Strategies, 2nd Volume - Melo, Luís; Azevedo, Andreia S. (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In biofilms, microorganisms are able to communicate together and assemble by themselves, creating a consortium with different properties from the original free-floating microorganisms. In fact, biofilm cells bind strongly to a living or non-living surface, enclosed in a self-produced extracellular matrix that is composed of extracellular polymeric substances. One benefit of this lifestyle is the increased resistance or tolerance to antimicrobial agents (e.g., antibiotics). Hence, research on the development of alternative strategies to prevent and control biofilms is highly relevant for society in terms of human health, industry and the environment. Different approaches to prevent or control biofilms using antibiotic alternative strategies were submitted to this Special Issue.